Metagenome changes in the biogas producing community during anaerobic digestion of rice straw. (August 2016) - Pore, Soham D.; Shetty, Deepa; Arora, Preeti; Maheshwari, Sneha; Dhakephalkar, Prashant K.
Highlights: Metagenome was sequenced to profile the microbial community and metabolism. Acid producing bacteria were abundant in sour digester. Abundance of methanogens was more prominent in healthy stage. Abstract: The present investigation was undertaken to study the microbial community succession in a sour and healthy digester. Ion torrent next-generation sequencing (NGS)-based metagenomic approach indicated abundance of hydrolytic bacteria and exclusion of methanogens and syntrophic bacteria in sour digester. Functional gene analysis revealed higher abundance of enzymes involved in acidogenesis and lower abundance of enzymes associated with methanogenesis like Methyl coenzyme M-reductase, F420 dependent reductase and Formylmethanofuran dehydrogenase in sour digester. Increased abundance of methanogens (Methanomicrobia) and genes involved in methanogenesis was observed in the restored/healthy digester highlighting revival of pH sensitive methanogenic community.